A new species of Triozocera pierce, 1909 (Strepsiptera: Corioxenidae) from Oman, with a new distribution record for Mengenilla arabica kinzelbach, 1979 (Strepsiptera: Mengenillidae) - Cook, JL; Al-Jahdhami, A; Kathirithamby, J (BioOne, 2022)
Triozocera longipalpis n. sp. is described as the first species in this genus from Oman and the Middle East. This species is readily separated from other species of Triozocera due to its unusually long and curved maxillary palp. Mengenilla arabica is reported for the first time from Oman and was previously only known from two collections, one from Saudi Arabia and one from Kuwait.